ANALISIS IMPLEMENTASI STRATEGI KOMUNIKASI BISNIS TERHADAP KEBERHASILAN USAHA PEDAGANG KAKI LIMA (STUDI KASUS PADA PEDAGANG KAKI LIMA DI SEPUTARAN ALUN – ALUN LAPANGAN MERDEKA DI KOTA PANGKALPINANG) - Novidya, Rika; Ruben Manullang, Rizal; Ahmad Agin, Arka’a (Jurnal Progresif Manajemen Bisnis, 2019)
"Analysis of the Implementation of Business Communication Strategies on the Success of Street Vendors’ Business (Case Study of Street Vendors in Alun-Alun Merdeka Square in Pangkalpinang City)". The purpose of this study was to determine the effect of business communication on the success of the business on street vendors in the vicinity of Alun - Alun Merdeka Square, Pangkalpinang City. This study also aims to increase the theoretical knowledge about the implementation of business communication strategies towards the success of the Street Vendors business in Alun - Alun Taman Merdeka in Pangkalpinang City. The theory used in this study is management theory and AIDDA strategy. The method used in this study is descriptive with a quantitative approach with the aim to find the influence of independent variables with dependent variables using a statistical formula that examines the relationship between the implementation of business communication strategies to the success of street vendors in the independent square in Pangkalpinang City. While the statistical formula used to test the hypothesis is Multiple Linear Regression Analysis. The population in this study were street vendors who were around Alun - Alun Merdeka Square in the city of Pangkalpinang, which numbered 1,200 people. From the calculation, the sample size is 60, but researchers have special criteria so that the sample in this study amounted to 30 people because sampling in this study was done by purposive sampling, which is to determine the research sample with certain considerations aimed at making the data obtained later representative or representative. Based on the results of the study prove that: (1) There is a significant effect of Attention, Interest, and Action towards PKL Business Success in Alun - Alun Merdeka City of Pangkalpinang. (2) The results of this study are also proven by the obtained Fcount value of 9.338. While the critical price of the Ftable value with numerator free 6 and the denominator 24 at (0.05) is 2.51. Thus Fcount (9.338)> Ftable (2.51), so clearly Ho is rejected and H1 is accepted as well if using a significant value comparison of 0.001.